PELATIHAN SOFTWARE MENDELEY GUNA PENINGKATAN KOMPETENSI MAHASISWA DALAM PENGUTIPAN KARYA ILMIAH - Fajar Ifan Dolly; Nanang Al Hidayat; M. Chotib; Muhammad Nasir; Ira Widyastuti; Deni Handani (Nusantara Hasana Berdikari, 2022)
This service activity aims to increase students' knowledge and insight, especially related to the ethics of scientific writing, improve the quality of scientific writing, and utilize the Mendeley application to make it easier for STIA SS students to make citations and bibliography for writing scientific papers.This training activity was encouraged because it wanted to provide opportunities for students to be able to master conceptually and practically in using the Mendeley software for citing and compiling bibliography automatically. To achieve the goals and targets of this service activity, the implementation of the activities uses the lecture, discussion, and practice methods so that training participants can easily understand the material given in the training. This training is carried out for final semester students who are compiling a final paper. It can be concluded that this training activity reaped very good results as the participants were able to operate the Mendeley application very well as it was in accordance with the targets and achievements specified. During the activity the participants also provided active feedback by asking questions and having discussions with the facilitator.